Evaluation of turbidity and dissolved organic matter removal through double filtration technology with activated carbon (2018)
The decrease of physicochemical and microbiological quality of surface supply source for human consumption, requires specific complementary treatments to ensure the supply of safe drinking water. This study evaluated the double filtration technology with two types of Granular Activated Carbon (GAC: vegetable-coconut and mineral-bituminous shells, respectively), to determine its influence in reducing turbidity and mainly dissolved organic matter (UV254). We used filtered water from a Conventional Water Treatment Plant (WTP) and the second filtration stage were made using continuous flow gravity columns at laboratory-scale with different percentages of GAC:sand (100:0, 80:20, 50:50, 30:70, and 0:100). While the sand filter presented the best turbidity removal efficiency, the CAG filters were more efficient at UV254 removal, being most efficient the filters with greater percentage of GAC. The results demonstrate that the use of double filtration technology with GAC can be an efficient alternative for the removal of organic matter to obtain safe drinking water.